Dipyridamole: a Controlled Trial of its Effect in Acute Myocardial Infarction. Issue 5627 (9th November 1968) - Gent, A. E.; Brook, C. G. D.; Foley, T. H.; Miller, T. N.
Abstract : A controlled trial of oral dipyridamole in 103 patients with acute myocardial infarction showed no difference in the number of complications or deaths in either the control or the treated groups. It is concluded that dipyridamole has no benefit in acute myocardial infarction.